A real-world stepped wedge cluster randomized trial of practice facilitation to improve cardiovascular care. (December 2015) - Liddy, Clare; Hogg, William; Singh, Jatinderpreet; Taljaard, Monica; Russell, Grant; Deri Armstrong, Catherine; Akbari, Ayub; Dahrouge, Simone; Grimshaw, Jeremy
Abstract Background Practice facilitation has been associated with meaningful improvements in disease prevention and quality of patient care. Using practice facilitation, the Improved Delivery of Cardiovascular Care (IDOCC) project aimed to improve the delivery of evidence-based cardiovascular care in primary care practices across a large health region. Our goal was to evaluate IDOCC's impact on adherence to processes of care delivery. Methods A pragmatic stepped wedge cluster randomized trial recruiting primary care providers in practices located in Eastern Ontario, Canada (ClinicalTrials.gov: NCT00574808). Participants were randomly assigned by region to one of three steps. Practice facilitators were intended to visit practices every 3–4 (year 1—intensive) or 6–12 weeks (year 2—sustainability) to support changes in practice behavior. The primary outcome was mean adherence to indicators of evidence-based care measured at the patient level. Adherence was assessed by chart review of a randomly selected cohort of 66 patients per practice in each pre-intervention year, as well as in year 1 and year 2 post-intervention. Results Eighty-four practices (182 physicians) participated. On average, facilitators had 6.6 (min: 2, max: 11) face-to-face visits with practices in year 1 and 2.5 (min: 0 max: 10) visits in year 2. We collected chart data from 5292 patients. After adjustment for patient and provider characteristics, there was a 1.9 % (95 % confidence interval (CI): −2.9 to −0.9 %) and 4.2 % (95 % CI: −5.7 to −2.6 %) absolute decrease in mean adherence from baseline to intensive and sustainability years, respectively. Conclusions IDOCC did not improve adherence to best-practice guidelines. Our results showed a small statistically significant decrease in mean adherence of questionable clinical significance. Potential reasons for this result include implementation challenges, competing priorities in practices, a broad focus on multiple chronic disease indicators, and use of an overall index of adherence. These results contrast with findings from previously reported facilitation trials and highlight the complexities and challenges of translating research findings into clinical practice. Trial registration ClinicalTrials.govNCT00574808